EVALUATION OF FORMAL RISK ASSESSMENT IMPLEMENTATION OF MIDDLE EAST RESPIRATORY SYNDROME CORONAVIRUS IN 2018 - Della Safera Pradanti (Universitas Airlangga, 2019)
Background: Confirmed cases of Middle East respiratory syndrome caused by coronavirus (MERS-CoV) were not found until the end of February 2019 in Indonesia. The spreading threat of MERS-CoV disease in Indonesia is still quite vast, mainly because of the amount of international travel from Indonesia to Saudi Arabia for the purpose of Hajj and Umrah, vacationing, working, or settling in the Arabian Peninsula. Purpose: The aim of this study is to evaluate the implementation of formal risk assessment (FRA) and MERS-CoV risk in Indonesia in 2018, having regard to threat, vulnerability, and capacity. Method: This study is a non-reactive observation study presented descriptively using the literature method and in-depth interviews with staff of the subdirectorat of Penyakit Infeksi Emerging Kementerian Kesehatan Republik. Decision-making for the threat category and vulnerability category is based on the highest threat index and vulnerability values, while the capacity category is based on the lowest capacity index value. Results: This study shows that there are three threat subcategories and two vulnerability subcategories that have high index scores and eight capacity subcategories that have low scores. Conclusion: The implementation of risk assessment for MERS-CoV with the FRA method as a whole has been maximally pursued. However, there are still shortcomings in the results of the research that need to be improved through further interventions to reduce the subcategory values that are high in the threat and vulnerability index and to increase the value of the low capacity index.